2008
DOI: 10.1007/s00792-008-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoates are essential for maintenance of redox state in the Antarctic bacterium Pseudomonas sp. 14-3 during low temperature adaptation

Abstract: Polyhydroxyalkanoates (PHAs) are highly reduced bacterial storage compounds that increase fitness in changing environments. We have previously shown that phaRBAC genes from the Antarctic bacterium Pseudomonas sp. 14-3 are located in a genomic island containing other genes probably related with its adaptability to cold environments. In this paper, Pseudomonas sp. 14-3 and its PHA synthase-minus mutant (phaC) were used to asses the effect of PHA accumulation on the adaptability to cold conditions. The phaC mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 38 publications
(38 reference statements)
4
112
0
Order By: Relevance
“…The genome of P. haloplanktis also reveals several insights into ROS protection such as deletion of ROS producing pathways, several occurrences of dioxygenases and the repair mechanisms of oxidized compounds (Medigue et al, 2005). Similar observations have been made in the genome and proteome of other psychrophilic microorganisms (Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Duchaud et al, 2007;Bakermans et al, 2007;Ayub et al, 2009;Piette et al, 2010), revealing a general constraint on these bacteria. However, we found that at 18 °C, another type of oxidative stress is induced by stimulation of metabolic activity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The genome of P. haloplanktis also reveals several insights into ROS protection such as deletion of ROS producing pathways, several occurrences of dioxygenases and the repair mechanisms of oxidized compounds (Medigue et al, 2005). Similar observations have been made in the genome and proteome of other psychrophilic microorganisms (Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Duchaud et al, 2007;Bakermans et al, 2007;Ayub et al, 2009;Piette et al, 2010), revealing a general constraint on these bacteria. However, we found that at 18 °C, another type of oxidative stress is induced by stimulation of metabolic activity.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the second group of proteins that displays the highest repression factors at 4 °C is represented by the oxidative stress-related proteins catalase (-6.5x), glutathione reductase (-8.1x) and peroxiredoxin (-15.7x). At first sight, this may be regarded as a conflicting result because conclusive evidences have indicated that psychrophiles are exposed to a permanent oxidative stress at low temperatures, which originates from improved dioxygen solubility and increased ROS stability (Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Duchaud et al, 2007;Bakermans et al, 2007;Ayub et al, 2009;Piette et al, 2010). In order to reconcile these apparent contradictions, it should be recalled that the general aerobic metabolism of the Antarctic bacterium is stimulated at 18 °C, also resulting in ROS production.…”
Section: Oxidative Stress-related Proteinsmentioning
confidence: 99%
“…Consequently, lipid peroxidation in the mutant strain was 25-fold higher after decrease of temperature. Hence, PHA metabolism controls the availability of the reducing equivalents NADH and NADPH, thus alleviating the oxidative stress caused by cold temperature, by supplying the reductive power necessary to subdue the oxidative stress induced by cold conditions via PHB degradation [89].…”
Section: Cryophilic [Psychrophilic] Pha Producersmentioning
confidence: 99%
“…This species shows high stress resistance and is able to synthesize large amounts of poly(3-hydroxybutyrate), the best-known member of a bacterial reserve polymers family known as polyhydroxyalkanoates (PHAs) (Ayub et al, 2004(Ayub et al, , 2009. PHAs are involved in bacterial survival under different stressful conditions (Ló pez et al, 1995;Kadouri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%